2018
DOI: 10.1016/j.neuroimage.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and extra-axonal axial diffusivities in the white matter: Which one is faster?

Abstract: A two-compartment model of diffusion in white matter, which accounts for intra- and extra-axonal spaces, is associated with two plausible mathematical scenarios: either the intra-axonal axial diffusivity D is higher than the extra-axonal D (Branch 1), or the opposite, i.e. D < D (Branch 2). This duality calls for an independent validation of compartment axial diffusivities, to determine which of the two cases holds. The aim of the present study was to use an intracerebroventricular injection of a gadolinium-ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 51 publications
12
44
0
Order By: Relevance
“…5,36 By comparison, in our spheric mean model, we explicitly estimated the extra-axonal hindered diffusivity, constraining it to be less than the intra-axonal parallel diffusivity, as suggested by independent validation of the compartment parallel diffusivities. 37 In our work, we also took advantage of the 300-mT/m maximum gradient strength accessible on the Connectom scanner. Higher gradient strengths have been shown to increase the sensitivity of diffusion MRI experiments to intra-axonal water diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…5,36 By comparison, in our spheric mean model, we explicitly estimated the extra-axonal hindered diffusivity, constraining it to be less than the intra-axonal parallel diffusivity, as suggested by independent validation of the compartment parallel diffusivities. 37 In our work, we also took advantage of the 300-mT/m maximum gradient strength accessible on the Connectom scanner. Higher gradient strengths have been shown to increase the sensitivity of diffusion MRI experiments to intra-axonal water diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of our method, in contrast to alternative SDE techniques, is the simplicity with which the intra‐axonal diffusivity is obtained. In fact, with the TDE approach, D a is the easiest parameter to determine rather than, as other studies have found, one of the most difficult . Once D a is known, then the axonal water fraction, f , can be readily calculated from Equation , which also requires data for the average b0 signal (i.e., SÂŻ0).…”
Section: Discussionmentioning
confidence: 99%
“…Parameters are estimated by fitting dMRI data, often using nonlinear optimization methods. In WM, one such parameter, intrinsic intra‐axonal diffusivity ( D a ), has proven especially challenging to measure . This is because D a estimates are sensitive to modeling assumptions and tend to be only loosely constrained by the data, although some recently proposed approaches seem to be more promising …”
Section: Introductionmentioning
confidence: 99%
“…20,21 This was done to model two scenarios: D ex, 0 < D in, 0 and D in, 0 < D ex, 0 , since it is not completely clear yet whether intra-axonal water is faster than extra-axonal water, although some preliminary evidence leans towards intra-axonal being faster. 48,49…”
Section: Spin Dynamicsmentioning
confidence: 99%